2017
DOI: 10.1038/onc.2017.88
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic effects of evolutionarily conserved noncoding RNA ECONEXIN on gliomagenesis

Abstract: Accumulating studies have demonstrated the importance of long noncoding RNAs (lncRNAs) during oncogenic transformation. However, because most lncRNAs are currently uncharacterized, the identification of novel oncogenic lncRNAs is difficult. Given that intergenic lncRNA have substantially less sequence conservation patterns than protein-coding genes across species, evolutionary conserved intergenic lncRNAs are likely to be functional. The current study identified a novel intergenic lncRNA, LINC00461 (ECONEXIN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 43 publications
2
81
0
Order By: Relevance
“…29 We also found that most of Rik-201, and part of Rik-203, are located in the cytoplasm (Figure 2A target in previous study 42 ( Figure S2B). 29 We also found that most of Rik-201, and part of Rik-203, are located in the cytoplasm (Figure 2A target in previous study 42 ( Figure S2B).…”
Section: Mir-96 and Mir-467a-3p Combine With Rik-201 And Rik-203 Resupporting
confidence: 78%
See 2 more Smart Citations
“…29 We also found that most of Rik-201, and part of Rik-203, are located in the cytoplasm (Figure 2A target in previous study 42 ( Figure S2B). 29 We also found that most of Rik-201, and part of Rik-203, are located in the cytoplasm (Figure 2A target in previous study 42 ( Figure S2B).…”
Section: Mir-96 and Mir-467a-3p Combine With Rik-201 And Rik-203 Resupporting
confidence: 78%
“…A recent study identified the novel Rik-201 and its homologous gene ECONEXIN and demonstrated its ceRNA functional role in gliomagenesis. 29 We also found that most of Rik-201, and part of Rik-203, are located in the cytoplasm (Figure 2A), which suggest they might function as the ceRNA. RNA pull-down experiments determined that miR-96 combined with Rik-201 ( Figure 2B), and miR-467a-3p combined with Rik-203 ( Figure 2C).…”
Section: Mir-96 and Mir-467a-3p Combine With Rik-201 And Rik-203 Rementioning
confidence: 60%
See 1 more Smart Citation
“…LncRNAs, e.g., NBAT-1 and Pnky, may regulate cell differentiation and development [ [20][21][22], reviewed in [23]]. LncRNA Rik-201 plays important role in gliomagenesis [24]. However, the role of LncRNAs on neural differentiation, the process where embryonic stem cells (ESCs) mature into specialized neural progenitor cells (NPCs), which is crucial for cognitive function, neural development and neurotoxicity [25], remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of lncRNA HOXA‐AS3 promotes tumor progression and predicts poor prognosis in glioma . A novel lncRNA ECONEXIN is a potential oncogene that regulates TOP2A by sponging miR‐411‐5p in glioma . LncRNA H19 regulates glioma angiogenesis and the biological behavior of glioma‐associated endothelial cells by inhibiting miR‐29a .…”
Section: Introductionmentioning
confidence: 99%